Influence of Level and Duration of Quantitative Feed Restriction on Post-Restriction Egg-Laying Characteristics and Egg Quality of Pullets - Ukachukwu, S.N.; Akpan, U.O. (International Journal of Poultry Science, 2007)
The effects of levels and duration of quantitative feed restriction on post-restriction egg-laying characteristics and egg quality as well as economics of egg production of pullets were investigated in a 2x7 factorial for completely randomized design experiment using 126 point-of-lay (POL) Olympia Brown commercial pullets, which had been subjected to various levels and durations of feed restrictions. The experiment lasted from 20th to 37th week of age but the actual period of data collection was from 30th to 37th week of age (that is, 8 weeks). The feeding regimens (treatments) were AFAF (ad libitum feeding from 20th week to 34th week - 14 weeks); AFRF1 (ad libitum feeding from 20th to 24th week (POL) – 5 weeks followed by 10% restriction feeding from POL to 34th week - 9 weeks); AFRF2 (ad libitum feeding from 20th to POL – 5 weeks followed by 20% restriction feeding from POL to 34th week - 9 weeks); RF1RF1 (10% restriction feeding from 20th to 34th week - 14 weeks); RF1AF (10% restriction feeding from 20th week to POL – 5 weeks followed by ad libitum feeding from POL to 34th week - 9 weeks); RF2RF2 (20% restriction feeding from 20th to 34th week - 14 weeks); and RF2AF (20% restriction feeding from 20th week to POL – 5 weeks followed by ad libitum feeding from POL to 34th week - 9 weeks). From 34th to 37th week of age, all the groups were reverted, on treatment basis, to ad libitum feeding (post-restriction period). Each treatment was replicated into three with six pullets per replicate. During the data collection period (30th – 37th week of age) one egg per replicate was collected three times per week for egg quality indices. Birds that were under feed restriction laid heavier first eggs but had lower (P<0.05) hen day production (HDP) than their ad libitum counterparts. Ad libitum fed birds transferred to 20% restricted feeding had the best economic indices. Birds subjected to restriction feeding had higher feed intake, poorer kg feed/dozen eggs, higher cost for dozen eggs (N) and lower gross margin (N) during post-restriction time (P<0.05) than when they were under restriction. On egg quality, birds had higher (P<0.05) haugh unit and albumen height but lower yolk index during restriction time than during post-restriction time. There were no significant differences in all the other quality indices